(3aJM GdbQjH GdeLjH aj TQM CdaGX GdJbQjHs - (3GdZRj, eMeO Hf bGSe Hf eMeO, J (B918 (3g`s
(3ChdgG (B:s
(3GdbGjd ef jQO Gddg HYO GdHSedI ; aj ZGjI Gg NjQG jabg aj GdOjf hYdi Bdg gPG cJGH aj ZGjI GdGNJUGQ hGdJgPjH hVYJg Ydi GdcJGH GdeSei HGdJbQjH adPdc SejJg HGSejf CMOgeG aJM GdbQjH GdeLjH aj TQM CdaGX GdJbQjH hGdKGfj Gdbhd GdeNJGQ aj TQM ZGjI GdGNJUGQs
(3BNQgG (B:s
(3hEf edc GdhWA (B( (3cPG (B) (3HGdfcGM GdCeI GdeWdbI HYO Pdc de JUQ Ce hQO dg HGdhWA aj GdfcGM hUGQJ Ce hdO dg HGdhWA HGdTHgI Ydi CMO Gdbhdjf hGdbhd GdKGfj dG JUjQ Ce hQO hgh GdQGLM aj GdePgHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 5s
(3eYLe GdeDdajf (B3 / 559s
(3EjVGM Gdecfhf (B2/ 136s
(3gOjI GdYGQajf (B2 / 300s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs